A week in winter - Binchy, Maeve (New York : Alfred A. Knopf, 2013)
Follows the efforts of Chicky who, with the help of Rigger and her niece Orla, turns a coastal Ireland mansion into a holiday resort and receives an assortment of first guests who throughout the course of a week share laughter and the heartache of respective challenges.
Follows the efforts of a woman who turns a coastal Ireland mansion into a holiday resort and receives an assortment of first guests who throughout the course of a week share laughter and the heartache of respective challenges.
"Originally published in Great Britain in slightly different form by Orion Books, London, in 2012"--T.p. verso.
Keywords: Bed and breakfast accommodations -- Fiction; City and town life -- Ireland -- Fiction; Ireland -- Fiction